An immobilized perylene diimide derivative for fucoidan purification from a crude brown algae extract - Zayed, Ahmed; Dienemann, Claudia; Giese, Christina; Krämer, Roland; Ulber, Roland (Process biochemistry, 2018)
A polycationic perylene diimide derivative was successfully immobilized to capture polysulphated fucoidan from a crude extract of F. vesiculosus. At a slightly acidic pH, immobilized perylene diimide derivative is positively charged and can form electrostatically-driven aggregates with more than 80% of fucoidan in only 16h, compared to 44h in recently developed immobilized toluidine blue. Purified fucoidan was identified by FTIR, which demonstrated typical IR bands in comparison with the commercial product. Moreover, it showed improved purity than crude type by a factor of 1.4 after purification. Pharmacologically, it prolonged APTT and TT, revealing a potential heparin-like anticoagulant activity by interfering with intrinsic and common blood coagulation pathway. Automated downstream and scale-up processes were further performed with developing a FPLC protocol. The new technique proved to be a competitor to immobilized toluidine blue for production of a high-grade fucoidan.